Design analysis of drainage system design on coal mining land - BAHARUDDIN, ICHSAN INVANNI; HAR, Rusli; ASSHIDIQQI, MUHAMMAD HABIB; ANARTA, RUDY; Tanjung, Denny Akbar (Jurnal Natural, 2025)
PT Bumi Bara Makmur Mandiri is a mining company engaged in coal mining, located in Hajran Village, Bathin XXIV District, Batang Hari Regency, Jambi Province. The company employs an open-pit mining method, which results in the formation of depressions that act as rainwater catchment areas, creating pools (sumps). To manage these sump areas effectively for mining activities, a mine dewatering drainage system is implemented. Over the past ten years, rainfall data indicates a catchment area of 246.02 hectares, with an estimated rainfall of 280.88 mm for a return period of ten years. The groundwater that accumulates in the pooling area has an inflow rate of 0.11 m/s, leading to a total water discharge entering PIT A of 39.12 m/second. Currently, there is one pump available with a power capacity of 10.83 kW to remove this water. Due to the significant water discharge, it is essential to design an economical open flow that can handle a flow rate of 2.96 m/s. Furthermore, a design for a holding pond is required, as the existing capacity is insufficient to accommodate the incoming water discharge, which hampers the sedimentation process. To address this, a redesigned settling pond with dimensions of 46 m x 36 m x 7 m and six compartments has been proposed. This solution will enhance the effectiveness of the mine drainage process